Pandemic Covid-19 And Audit Quality Of Public Accountant Firm In East Jakarta - Budiandru (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
The public accounting profession is responsible for increasing the reliability of the company's financial statements so that the public can obtain reliable financial information as a basis for decision making. This study analyzes independence and competence in audit quality with audit risk as a moderating variable. Pandemic affects most of the business processes carried out by public accounting firms, be it internal management, to reconsider audit engagements to alternative audit approaches that must be taken in a pandemic. Respondents in this study are auditors who work at the Public Accounting Firm in East Jakarta. The number of auditors who were the sample of this study was 250 respondents consisting of auditors from the public accounting firm. The method used in this research is multiple linear regression analysis. The results showed that competence had a significant effect on audit quality. Auditors need to increase additional knowledge by participating in training and professional courses so that their competencies are increasingly developing.